Comparison of bacterial densities and resistance in different beach compartments: should water be our main concern? - Del Busso Zampieri, Bruna; Sanches de Oliveira, Raphaela; Bartelochi Pinto, Aline; da Costa Andrade, Vanessa; Barbieri, Edison; Merguizo Chinellato, Roberta; Fernandes Cardoso de Oliveira, Ana Júlia (O Mundo da Saúde, 2017)
Coastal regions are very important, since they provide food, enable economic and leisure activities however, the increase in urbanization of coastal areas are accompanied by great volumes of organic effluent, which is sometimes discharged in natura in water bodies, increasing the risk of the presence of pathogenic resistant bacteria in marine environments. In fact, recent studies showed higher bacterial densities in sediments than in water, since its present more favorable conditions for bacterial survivor (e.g. sun protection and predation). In addition, bivalves tend to accumulate suspended bacteria from the water, since they are filter feeding organisms. Thus, the present study evaluated densities and resistance to antibiotics of Enterococcus sp., Escherichia coli and Aeromonas sp. in water, sediment and mussels samples. Samples were collected at Praia dos Sonhos (Itanhaém) and Ubuqueçaba Island (Santos). Bacterial densities were determined by Membrane Filter Technique and the isolated strains were submitted to antibiotic sensibility test. Bacterial densities were lower in water and higher in sediments and mussels samples. Bacterial strains from Santos presented higher frequencies of resistance than those isolated from Itanhaém (less impacted area). Aeromonas strains were more resistant to Cefalotin and Cefuroxin, Enterococcus to Gentamicin and Streptomicin, and E. coli to Vancomicin and Eritromicin. The results obtained point to the need to establish public policies, laws and monitoring programs about the microbiological quality of mollusks and sediments, including the use of Enterococcus sp as microbiological indicator as well as about the resistance of the bacteria present in these environments.